HORIZONTAL MARKETING IN CLUSTERS: NETWORK APPROACH FOR THE INTERNATIONALIZATION OF SMES IN GOLD - Bueno Fajardo, Tatiana Madelaine; Correa Toledo, Luisa Anabel; Suárez Solórzano, Tatiana Mercedes; Benitez Luzuriaga, Francisco Vladimir (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
The network approach as a model tries to overcome the deficiencies of the differentiated orders in agglomeration of the institutions, in this way they focus on achieving the optimal relationship between many of its components. This serves to understand the behavior of companies, the study analyzes the theoretical basis of horizontal marketing and the approach of networks in micro, small and medium enterprises established in developed countries. Likewise, the results of the research show through the correlation of the hypotheses raised, that in the countries of emerging economies such as Ecuador, the process of internationalization of those of micro, small and medium enterprises can have good results if strategies of Horizontal marketing with a network approach.